2019
DOI: 10.35940/ijeat.a9762.109119
|View full text |Cite
|
Sign up to set email alerts
|

Test Case Design and Test Case Prioritization using Machine Learning

Abstract: Designing and prioritizing test cases is a very tedious task. Given all the advancements in the world of software testing, on any given day engineers spend several man-hours to identify all possible testing scenarios and preconditions attached with it. Test engineers then use the scenarios and preconditions to write multiple test cases. Every test case has a template skeleton to follow - expected results, actual results, priority, test suite category classification (regression, sanity, smoke, integration, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The graph can update itself after each cycle so that cycles would affect the order of test cases. Sharma and Agrawal built an information graph from UML and user story, then fed that graph into metaheuristic algorithms [14]. Kaur et al extracted the elements of UI in each test step, then used this data as input for traditional machine learning algorithms (SVM, decision trees, naive Bayes, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…The graph can update itself after each cycle so that cycles would affect the order of test cases. Sharma and Agrawal built an information graph from UML and user story, then fed that graph into metaheuristic algorithms [14]. Kaur et al extracted the elements of UI in each test step, then used this data as input for traditional machine learning algorithms (SVM, decision trees, naive Bayes, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…The work in [26] uses regression trees to minimize test case redundancy in CI testing and improve the costeffectiveness of CI. Very recent work in [27] proposes machine learning for the generation and prioritization of test cases for a user interface. Their approach concludes that K-Nearest Neighbors performed well among the rest of the machine learning classification models on their collected historical data from user interface design.…”
Section: Related Workmentioning
confidence: 99%
“…Rongqi et. al [8] surveyed ML-based TCP techniques and reported that existing ML-based papers investigated a wide variety of ML techniques including reinforcement learning [2], [23], [4], [3], [43], [44], [45], clustering [46], [47], [48], [49], [50], [51], [52], ranking models [23], [21], [31], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], and natural language processing [49], [21], [55], [63], [64]. However, each study only used a small number of features that are either easily collected or publicly published by existing work.…”
Section: Related Workmentioning
confidence: 99%